The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1164/rccm.201105-0848oc
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Recovery Predicts Clinical Worsening in Patients with Pulmonary Arterial Hypertension

Abstract: HRR1 after 6MW test is a strong predictor of clinical worsening and TCW in patients with IPAH. The addition of HRR1 to 6MWD increases the capacity of 6MWD to predict clinical worsening and TCW in patients with IPAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(112 citation statements)
references
References 41 publications
10
99
2
1
Order By: Relevance
“…Attention has recently been focused on neurohormonal alterations in PAH patients and abnormalities of the sympathetic nervous system, similar to those described in left ventricular dysfunction [5,6,17]. Our clinical findings correlate with the accumulating evidence of sympathetic overactivation in patients with …”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Attention has recently been focused on neurohormonal alterations in PAH patients and abnormalities of the sympathetic nervous system, similar to those described in left ventricular dysfunction [5,6,17]. Our clinical findings correlate with the accumulating evidence of sympathetic overactivation in patients with …”
Section: Discussionsupporting
confidence: 81%
“…In this context, we reported that patients with IPAH had a reduced TtCW if they had reduced heart rate recovery (HRR) after 6MWT [6]. Interestingly, the reduced HRR was associated with a reduced chronotropic response during 6MWT and the majority (67%) of the patients taking β-blockers had a reduced HRR.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…It has been theorized that nocturnal hypoxia may cause increased catecholamine release possibly leading to autonomic dysfunction (38)(39)(40), which is known to be associated with mortality (41)(42)(43). HRR after stress testing has been well recognized as a measure of autonomic function (44) and a risk factor for adverse clinical outcomes in several disease states (48,49). Maeder and colleagues (50) studied HRR in patients with OSA and concluded that the severity of OSA, as defined by the AHI, was independently associated with abnormal HRR.…”
Section: Discussionmentioning
confidence: 99%
“…Such abnormalities may be visible in heart rate response during recovery from exercise and readily measured in variables such as HRR1, which is the fall in HR during the first minute of recovery. Minai et al [153] have measured this following a 6MWT in idiopathic PAH and found it to complement the ability of 6MWD to predict clinical worsening. Similarly in an older study with a limited multivariate analysis on a small cohort (n = 34) [154], the size of fall in S p O 2 during the 6MWT was found to be of prognostic value with a 27% increase in risk of death over the study period (1992-1997) for each percentage point fall in saturation.…”
Section: Field Exercise Testsmentioning
confidence: 99%